The English Passive Voice and its translation into Belarusian - Brutskaya, Alina A. (Journal of the Belarusian State University. Philology, 2019)
The paper observes the lexical and grammatical features of analytical forms of the Passive Voice. A special emphasis hereof is posed on the rationale for usage of grammar transformations by translating English Passive Voice constructions into Belarusian. The frequency rates of usage of different Passive Voice constructions in English and Belarusian are given. The research contemplates the stories written by A. C. Doyle and their translations made by various authors. It is devoted to the analysis of translation patterns of Passive Voice forms according to the types of passive constructions and sentences, in which they perform their lexical and grammatical functions. The main ways of translation of analytical passive forms from English into Belarusian are outlined.
Keywords: analytical forms; analytical forms of the passive voice; passive voice; passive constructions; translation; English to Belarusian translation; types of translation